Implementation of API Programming In Company Profile Applications Based On Android Mobile - Mirza Tirtonadji MirzaTn (NAROTAMA UNIVERSITY, 2021)
Company Profile as an image builder and carries a big goal in building university identity. From the point of view of the public and prospective new students, the company profile represents the university in showing various sides that it is proud of and has achieved that will determine how the university develops in the future, considering that other universities see a university from how they build their image. The development of the use of mobile android in the company profile brings new challenges how the capacity of the information produced will be more attractive to prospective students. Narotama University Surabaya as an international-scale campus in education requires this capacity in its company profile so that the company profile not only displays the university profile but can also guide prospective students in various university agendas.